Global oil price swings: Has their effect on Malta changed over time? - Germano Ruisi (Central Bank of Malta, 2023)
This paper develops a two-block Structural Vector Autoregression featuring time-varying parameters and stochastic volatility to estimate the changing spillover of global oil shocks into the Maltese economy during the period that goes from January 2008 to March 2022. The model is estimated by using Bayesian methods and focuses on the effect on Maltese output and prices. The results evidence how Great Recession and COVID-19 pandemic are associated with higher inflation responsiveness. Notwithstanding, the response of energy inflation gradually declines and, as a consequence, the medium-term pass-through from international to domestic energy prices decreases from 1% to virtually zero in response to a shock rising real oil prices by 10%. Finally, the recent surge in global energy prices generated short-lived negative responses in domestic output as a result of the energy subsidies implemented by the Maltese government.
Keywords: C15; E31; E32; Q43; 330; Bayesian Structural VAR; time-varying parameters; stochastic volatility; block exogeneity; oil shocks; shock spillover